Chemical Constituents of the Bark of Zanthoxylum gilletii (Rutaceae) and Their In Vitro Antiplasmodial and Molecular Docking Studies - Liliane Clotilde Dzouemo; Gervais Mouthé Happi; Sikiru Akinyeye Ahmed; Willifred Dongmo Tekapi Tsopgni; Michael Nde Akuma; Shina Salau; Emmanuel Ngeufa Happi; Jean Duplex Wansi (Journal of Chemistry)
The phytochemical investigations of the methanol extract of Zanthoxylum gilletii bark led to the isolation of thirteen compounds identified as two alkaloids including one acridone 5-hydroxynoracronycine (1) and one benzo [c] phenanthridine decarine (2), three lignans trans- and cis-fagaramide (3 and 4) and sesamin (5), two coumarins scoparone (6) and scopoletin (7), three pentacyclic triterpenoids fridelin (8), lupeol (9) and erythrodiol-3-O-palmitate (10), one phenolic compound vanillic acid (11) as well as two common steroids stigmasterol (12), and its derivative stigmasterol-3-O-β-D-glucopyranoside (13). The structures of all the isolated compounds were elucidated by means of their spectroscopic and spectrometric data (1D, 2D-NMR, MS) as well as the comparison of these data with those reported in the literature. Except for compounds 9 and 11–13, all the other isolated compounds are reported for the first time from Z. gilletii but have been already obtained from other Zanthoxylum species and in the Rutaceae family. Compounds 1, 3–5, and 9 were tested in vitro for their antiplasmodial potencies against Plasmodium falciparum 3D7, and the results revealed that all the tested compounds displayed an inhibition between 51.89% and 54.69% while only the mixture of 3 + 4 gave an IC50 lower than 10 000 nM (IC50 = 1333 nM). Furthermore, all the compounds have been evaluated in silico for their ability to inhibit the Plasmodium falciparum dihydroorotate dehydrogenase 5TBO. Sesamin (5) showed the greatest affinity to the antiplasmodium receptor than artemether® and chloroquine®. Further recorded data from their ADMET study, as well as their chemotaxonomy, are also discussed herein. The present study provides further information to enrich the chemistry of Z. gilletii and its qualification as an important source for good candidates in new antiplasmodial drug development.